An integrated model approach for disaster impact reduction: lessons from a slow onset disaster in Chile - David Gomez-Schwartz; Mauricio Castillo-Vergara; Oscar Contreras González; Cesar Espíndola Arellano (Journal of Humanitarian Logistics and Supply Chain Management)
Purpose – The prolonged drought in Chile’s Coquimbo region has created a permanent state of emergency, forcing the state to spend millions each year distributing drinking water to rural communities. The purpose of this article is to detail a study focused on optimizing the supply of drinking water through trucks in the 15 communes of the region and how the problem was faced in a context of a slowonset disaster. Design/methodology/approach – A geo-referenced census and optimization analysis of the 5.541 households that receive drinking water was conducted to determine the feasibility of removing trucks from the system. To generate a greater reduction in distribution costs, it was suggested to incorporate water distribution infrastructure projects, changing the concept of ‘expenses’ to ‘investment’. Findings – The study was born out of the concern for the increased demand for drinking water from rural areas. The proposed and implemented framework allowed an additional 20% reduction in the initial transportation costs; this confirmed the assumption that the proposed optimization model alone would not offer a robust solution and was complemented and integrated with this type of alternative, forming an “integrated model”. Research limitations/implications – The paper has implications for the resilience of territories affected by climate change. Practical implications – The methodology can be replicated in other areas where similar interactions occur. Social implications – Families impacted by drought can improve their quality of life and reduce distress in the face of the constant emergency. Originality/value – This research aims to contribute knowledge from the perspective of a slow-onset disaster where water resources are scarce. It presents a framework where two disciplines converge, resulting in an “integrated model” that, through its implementation, reduces the costs of resource delivery while simultaneously improving the sanitary conditions of the beneficiary families.